Engineered clearing agents for the selective depletion of antigen-specific antibodies - Siva Charan Devanaboyina (Nature Portfolio, 2017)
The depletion of antigen-specific, deleterious antibodies during therapy and diagnosis remains an unsolved challenge. Here the authors develop ‘Seldegs’, antigens linked to human Fc fragments with high affinity for the neonatal Fc receptor FcRn, to deplete MOG- and HER2-specific antibodies in mice.